MUT‘AH DALAM CERAI GUGAT DI INDONESIA: TELAAH KEADILAN PERSPEKTIF MAQASHID SYARI‘AH - Hidayat, Rahmat; Irham, M. Iqbal; Pagar, Pagar (Smart Education, 2026)
Abstract: This study examines the discourse on mut‘ah in divorce initiated by the wife in Indonesia, which is not explicitly regulated in statutory law or the Compilation of Islamic Law (KHI). According to Article 158 of the KHI, the right to mut‘ah is granted only to wives divorced by their husbands (talaq), not to wives who file for divorce. This research employs a normative juridical method by analyzing statutory regulations such as Marriage Law No. 1 of 1974 and the KHI, and by comparing them with classical Islamic jurisprudence (fiqh). This approach is combined with an analysis of justice from the perspective of maqashid shari‘ah. The findings indicate that mut‘ah may be granted to a wife in cases of cerai gugat as long as the wife is not nusyuz. Granting mut‘ah to a wife who initiates divorce is viewed as an implementation of justice and as an effort to protect women’s rights in the aftermath of divorce. This study recommends regulatory reform of both statutory law and the KHI regarding the provision of mut‘ah in cases of cerai gugat, in accordance with the values of justice within Indonesian Muslim society. Keywords: mut‘ah, divorce initiated by the wife, KHI, maqashid shari‘ah, marriage. Abstrak: Penelitian ini membahas diskursus mut‘ah dalam cerai gugat di Indonesia yang tidak diatur secara eksplisit dalam undang-undang dan Kompilasi Hukum Islam (KHI). Menurut Pasal 158 KHI, hak mut‘ah hanya diberikan kepada istri yang diceraikan oleh suaminya (talak), bukan kepada istri yang mengajukan perceraian. Metode yang digunakan adalah yuridis normatif dengan menelaah peraturan perundang-undangan seperti UU Perkawinan No. 1/1974, KHI dan membandingkannya dengan fikih. Pendekatan ini dipadukan dengan analisis keadilan dalam perspektif maqashid syarī‘ah. Hasil penelitian menunjukkan bahwa pemberian mut‘ah dapat diberikan kepada istri dalam kasus cerai gugat selama istri tidak nusyuz. Pemberian mut‘ah kepada istri yang melakukan cerai gugat dipandang sebagai implementasi keadilan serta sebagai upaya melindungi hak perempuan akibat perceraian. Penelitian ini merekomendasikan perubahan regulasi terhadap undang-undang dan KHI dalam kasus pemberian mut‘ah dalam cerai gugat sesuai dengan nilai keadilan dalam masyarakat Muslim Indonesia. Kata Kunci: mut‘ah, cerai gugat, KHI, maqhasid syari’ah, perkawinan.